Canaidia - Murphy, Eveleen (2008)
Registrar's Collection.
Acrylic on Board.
Acquired from CIT CCAD Honours Fine Art and Ceramic Design Degree Show 2008 (Soup).
Contact CIT Arts Office for viewing arrangements
Keywords: Painting